The Effect of Human Resource Competencies on the Quality of Financial Statements - Syahputri, Yuni; Sakti, Indra; Sabrina, Hesti (Lembaga Jurnal & Seminar Universitas Pembangunan Panca Budi, 2024)
This study aims to determine the effect of human resource competence on the quality of financial statements. The population in this study is the Medan City Market Regional Company. While the respondents of this research are the accounting / financial management as many as 38 employees. The analysis method used is Simple Linear Regression analysis. After analyzing the data, conclusions can be drawn, namely: The results of the study using the t test state that there is an influence between Human Resource Competencies (HR) on the Quality of Financial Statements. In other words, if the HR competency variable increases, the quality of financial reports will increase.